IMPLEMENTASI KEBIJAKAN PENANGGULANGAN BENCANA BANJIR ROB DI KOTA SEMARANG - Zulfan, Fajril Izza; Manar, Dzunuwanus Ghulam (Journal of Politic and Government Studies, 2024)
The problem of floods and robs is the main problem in Semarang City which until now has not found the right solution to overcome it. In fact, there is a Semarang City PERDA to overcome disasters. So this study is designed to analyze how to implement flood and rob disaster management policies in Semarang City. This research is a descriptive qualitative research, with data collection in the form of interviews, observations, and documentation. The researcher uses a qualitative method because it is descriptive so that the researcher approaches intensely with informants to obtain data to analyze the implementation of flood and rob policies in Semarang City as well as the causes and efforts that have been made by the Semarang City Government in flood and rob disaster management. The theory used in this study is a policy implementation theory from Grindle in Nawawi (2009) which includes the context of implementation and the content of policy. The results of this study show that the causes of flood and rob problems in Semarang City are caused by natural and human factors, which include high rainfall, sedimentation due to land conversion, land subsidence due to excessive groundwater use, and clogging of the drainage system due to garbage. The Semarang City Government overcomes the problem of flooding and rob only the end of pipe approach to solve the problem downstream without the root or upstream of the problem